1977
DOI: 10.1128/aac.12.1.107
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Three Iodine-Containing Compounds as Antiplaque Agents

Abstract: The antibacterial activity of three iodine-containing compounds was determined for strains of four dental plaque-forming microorganisms, using an in vitro preclinical plaque model system. Solutions of inorganic iodine, povidone-iodine, and Wescodyne were tested for antiplaque activity against preformed plaques of a number of strains of Streptococcus mutans, Streptococcus sanguis, Actinomyces viscosus , and Actinomyces naeslundii . Solutions of inorganic iodine we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…The adhesive, dense character and the chemical nature of plaque apparently constitute a diffusion barrier to antiseptics (42,43), which may account for the inability of a number of established bactericidal agents to be effective in controlling dental plaque (6,17,43). Freely suspended plaque-forming microorganisms are orders of magnitude more susceptible to chlorhexidine than intact plaques of the same bacteria (42), supporting this view.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The adhesive, dense character and the chemical nature of plaque apparently constitute a diffusion barrier to antiseptics (42,43), which may account for the inability of a number of established bactericidal agents to be effective in controlling dental plaque (6,17,43). Freely suspended plaque-forming microorganisms are orders of magnitude more susceptible to chlorhexidine than intact plaques of the same bacteria (42), supporting this view.…”
Section: Resultssupporting
confidence: 60%
“…It has previously been demonstrated that serial dilution methods are inappropriate for testing the efficacy of agents against plaque microorganisms. Such methods require the presence of the agent for a prolonged period, a situation unlikely to occur in the mouth, and they do not take into account the diffusion barriers apparently existing in intact dental plaque (40,42,43). Thus, broth dilution techniques were demonstrated to overestimate the potency of agents by several orders of magnitude (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, agents were tested here by short-term immersion of preformed plaques in various agents employing an in vitro preformed-plaque model system. The methods were previously detailed (30)(31)(32)(33). Briefly, in vitro plaques were rinsed free of broth in demineralized water and then immersed in 10 ml of aqueous solution of the various test or control agents, at pH 6.8 to 7.0, for various durations and frequencies.…”
mentioning
confidence: 99%
“…Using a mouthwash containing chemotherapeutic agents would be a simple way to prevent dental caries by controlling the numbers of these microorganisms. For a long time, various compounds have been studied for possible use in plaque and caries control (4,12). Among these agents, chlorhexidine, a bisbiguanide compound, has been shown to exert antimicrobial and/or antiplaque effects (10).…”
mentioning
confidence: 99%